2005
DOI: 10.1586/14787210.3.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin: a nonabsorbable rifamycin antibiotic for use in nonsystemic gastrointestinal infections

Abstract: Rifaximin is a poorly water-soluble and minimally absorbed (<0.4%) rifamycin with in vitro activity against enteric Gram-negative bacteria including enteric pathogens. Fecal levels of the drug after 3 days' oral therapy exceed 8000 microg/g. Rifaximin is effective in the treatment and prevention of travelers' diarrhea due to Escherichia coli-predominant bacterial pathogens. It shows lower activity against dysenteric forms of bacterial diarrhea. The drug may be useful in other enteric infectious diseases, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 40 publications
1
61
0
1
Order By: Relevance
“…Rifaximin is a poorly absorbed oral antimicrobial agent that is concentrated in the gastrointestinal tract [33][34][35]. Rifaximin has a broad-spectrum of activity against gram-positive and gram-negative aerobic and anaerobic enteric bacteria [36][37][38].…”
Section: Rifaximin Regulates the Expression Of Detoxification Genes Imentioning
confidence: 99%
“…Rifaximin is a poorly absorbed oral antimicrobial agent that is concentrated in the gastrointestinal tract [33][34][35]. Rifaximin has a broad-spectrum of activity against gram-positive and gram-negative aerobic and anaerobic enteric bacteria [36][37][38].…”
Section: Rifaximin Regulates the Expression Of Detoxification Genes Imentioning
confidence: 99%
“…4,[35][36][37][38][39][40] Each of these drugs is approved in the United States for other types of gastrointestinal infections, and some clinicians have used either alone or in combination with metronidazole or vancomycin in patients with severe or recalcitrant CDAD. There are several small case reports addressing the potential efficacy of using adjuvant agents such as i.v.…”
Section: Management Of Cdadmentioning
confidence: 99%
“…Newer approaches include long, tapered or pulsed courses of vancomycin, as well as combination or sequential dosing with either rifaximin or nitazoxanide. [1][2][3][4][5]30,[35][36][37][38][39][40][41][42][43] An algorithm outlining our own approach is shown in Figure 2.…”
Section: Management Of Cdadmentioning
confidence: 99%
“…15 On the other hand, rifaximin is a poorlyabsorbed broad spectrum antibiotic with very few systemic side effects and at low risk of inducing bacterial resistance. 16,17 These properties make rifaximin an ideal antibiotic for the treatment of patients with HE as several studies have shown a significant decrease in plasma ammonia levels [18][19][20] with minimal impact on the normal gastrointestinal flora. 16 Many small studies have suggested that rifaximin is effective in treating acute HE and is extremely well tolerated.…”
Section: Introductionmentioning
confidence: 99%